Characterization of the novel HLA‐C*03:302 allele by sequencing‐based typing. (18th December 2018) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐C*03:302 differs from HLA‐C*03:249 by one nucleotide substitution at codon 99 in exon 3.